The Kenotic Theology of Anthony Bloom Metropolitan of Sourozh (1914-2003), in Anthropological Perspective - Rytsar, Roman (Université Saint-Paul / Saint Paul University, 2012)
Statement of the Problem - Metropolitan Anthony (Bloom) of Sourozh (1914-2003; henceforth: AB) was one of the leading Russian Orthodox voices of the 20th century and was widely known for his vast output of talks and sermons on the scriptures, spiritual life and contemporary issues. Some of this material was published during his lifetime but the majority has only become available after his death. Much of it remains to be translated from Russian. The inheritance of AB has not yet been properly studied and this doctoral dissertation is an initial attempt to sort through this huge body of material and begin to examine key themes. This thesis addresses the kenotic theology of Metropolitan Anthony. His unique insights in this one area are used as a lens through which to present his larger corpus of writings and their implications for Eastern Christian anthropology in our time. Kenotic theology was a particular focus of 19th and 20th century Russian theology. The consistent focus of AB’s kenotic theology is Christ’s God-forsakenness on the cross: “My God, my God why have you forsaken me?” (Mk 15:34). These words became a motto for Metropolitan Anthony’s life and preaching. In my research, I demonstrate that he developed a unique understanding of Christ’s God-forsakenness that was fundamental to his understanding of 1) kenotic theology and 2) what it means to be a human being. Because death, according to AB, is a “Godless” place, God entered precisely there, where He is not, in order to show true and deep solidarity with human beings and thus to bring salvation. Christ’s experience of God-forsakenness is, therefore, the deepest expression of God’s love and the key revelation of God’s faith in the human person. This is the central, creative, and original contribution that I believe AB makes to Eastern Christian theology today. // Methodology - There are a number of recurring topics in AB’s many talks: faith and atheism; spiritual life; marriage and family; priesthood and pastoral aspects; and sacraments and the Church. In this dissertation AB’s two central ideas are used as the keys to reading and analyzing this diverse material, namely the God-forsakenness of Christ (kenotic theology) and God’s faith in the human person (anthropology). As this appears to be the first doctoral research on the legacy of AB, the dissertation concentrates on a clear and full presentation of his kenotic thought, and leaves to others (or to later study) a more comparative, discursive analysis and evaluation of his theology. Here, the multiple threads of AB’s thought are gathered into a coherent tapestry (a project which has not yet, to my knowledge, been undertaken) using a synchronic, thematic mode of analysis. By employing AB’s characteristic notion of kenoticism as a hermeneutic lens, I present the underlying unity of his thought as seen throughout the discourses, which are currently available. Having first established what kenoticism denotes, both within the Orthodox tradition and in the wider Christian theological tradition, the distinctive features of AB’s kenotic theology as they emerge throughout his work are examined to answer the following two questions: what did AB say in his kenotic theology and how did he apply kenotic theology in practice? The dissertation is divided into two broad sections: theoretical and practical. In the first three chapters (theoretical) I compile and describe the background and possible roots of AB’s kenotic approach. Here AB’s kenotic theology is classed into two major themes: the God-forsakenness of Christ (kenosis) and God’s faith in the human person (anthropology). In the last two chapters (practical), using AB’s argumentation, I present the application of his kenotic theology and show how it is linked to the theoretical part of the thesis. In this practical section I first search AB’s work for “places” where a human being might experience abandonment by God and how AB applies God’s faith in the human person to address these circumstances. Second, I examine how the kenotic way of life, in AB’s understanding, brings a person to genuine encounter with another human being, with oneself and with God. // Main Points and General Conclusions - As noted above, Bloom’s original contribution is his conviction that Christ’s experience of God-forsakenness is the deepest expression of God’s love and the key revelation of God’s faith in the human person. But this dissertation also shows that AB’s kenotic theology has something practical and pastoral to offer contemporary people. First, AB underlines the need of every human being to rediscover authentic self-love. Here he made a clear distinction between selfish egoism and the true understanding of love for oneself that is the foundation for love of God and others. Secondly, AB’s kenotic theology offers Christians a practical tool for life with God and other people that is based on faith in the other person. As AB puts it: “If God believes in me, then I can believe in the other person. And if I believe in the other person, then the other person can believe in himself and in God.” AB was not naïve and realized that being fully trustful in all circumstances is impossible. But he was convinced that despite the sins of a human being there remains within him the indestructible image of God. And only by experiencing that full conviction from someone else could they learn about God’s faith and begin to love themselves and others. According to AB, relationships with God and with other people have some elements in common, such as moments of dryness, absence, abandonment and, as a result, loneliness. What does a human being have to do in these moments when he personally experiences or sees these moments being experienced by other people? In both cases AB teaches that he or she has to follow the example of Christ. In the first case, in his own despair, he has to remain faithful to the promises made to Christ in the past. In the second case, one must be ready to descend together with Christ into Hades with the other person who is suffering these difficult moments. Christians are called to be present in solidarity with others in their most difficult moments because Christ gave the ultimate example of being in solidarity with God and with people.
Keywords: kenotic theology; Metropolitan Anthony; kenosis; kenoticists; Anthony Bloom; Roman Rytsar; Tareev; Khrapovistky; Bulgakov; Lossky; Soloviev; Florovsky; God-forsakenness; Godlessness; Godforsakenness; atheism; self-love; God's faith; God believes